Structural change and charge compensation mechanism for Li1+x(Fe0.1Ni0.1Mn0.8)1-xO2 (0 < x <1/3) positive electrode material during electrochemical activation. (May 2022) - Tabuchi, Mitsuharu; Sasaki, Yoshikazu; Shibuya, Hideka; Doumae, Kyousuke; Katayama, Misaki; Yamanaka, Keisuke; Inada, Yasuhiro; Yuge, Ryota; Kubota, Kei
Highlights: Two 10% Fe- and Ni-substituted Li2 MnO3 samples were prepared for characterization. Sample calcined in N2 atmosphere had better electrochemical performance. Calcination in N2 atmosphere suppress cubic spinel formation on charging. Both samples utilize trivalent Fe ion as a redox center. Oxide ion acts as a redox center but it has poor reversibility. Abstract: Samples containing 10% Fe- and Ni-substituted Li2 MnO3 calcined in air and N2 were prepared and characterized. The sample calcined in N2 atmosphere exhibited higher initial capacities than the sample calcined in air. X-ray and electron diffraction data showed that calcining in N2 suppressed the formation of cubic spinel at the end of charging. The 57 Fe Mössbauer spectra showed that the sample calcined in N2 effectively utilizes Fe 3+ ions as a redox center. The Mn L-edge and Mn K-edge XANES spectra of the same sample showed that it underwent partial reduction to the trivalent state during discharging. The Ni K-edge XANES spectra indicated that oxidation or reduction did not occur. The O K-edge XANES spectra revealed the irreversible reaction of the oxide ion as a redox center. The development of a more practical synthetic process resulted in both samples showing promise as high-capacity materials for the positive electrode. Graphical abstract: Image, graphical abstract